The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1046/j.1432-1327.1999.00357.x
|View full text |Cite
|
Sign up to set email alerts
|

Difference between active and inactive nucleotide cofactors in the effect on the DNA binding and the helical structure of RecA filament

Abstract: The RecA protein requires ATP or dATP for its coprotease and strand exchange activities. Other natural nucleotides, such as ADP, CTP, GTP, UTP and TTP, have little or no activation effect on RecA for these activities. We have investigated the activation mechanism, and the selectivity for ATP, by studying the effect of various nucleotides on the DNA binding and the helical structure of the RecA filament. The interaction with DNA was investigated via fluorescence measurements with a fluorescent DNA analog and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…2B), and was 1.6‐fold larger than that of the complex without nucleotide. The effect of ADP on the HsRad51‐poly(dɛA) complex differs from that on the RecA‐ or XRad51‐poly(dɛA) complexes: ADP strongly decreases the fluorescence from the RecA‐poly(dɛA) complex (Ellouze et al . 1999), and does not significantly change that of the XRad51‐poly(dɛA) complex (Maeshima et al .…”
Section: Resultsmentioning
confidence: 99%
“…2B), and was 1.6‐fold larger than that of the complex without nucleotide. The effect of ADP on the HsRad51‐poly(dɛA) complex differs from that on the RecA‐ or XRad51‐poly(dɛA) complexes: ADP strongly decreases the fluorescence from the RecA‐poly(dɛA) complex (Ellouze et al . 1999), and does not significantly change that of the XRad51‐poly(dɛA) complex (Maeshima et al .…”
Section: Resultsmentioning
confidence: 99%
“…In vitro , other nucleotide triphosphates are competitive inhibitors of dATP‐promoted RecA coprotease activity (Weinstock and McEntee, ; Weinstock et al, ). It was suggested that the chemical nature of the nucleobase is important for the stability of the RecA‐ssDNA complex: adenine promotes strong RecA‐DNA binding, while other bases promote only weak binding, leading to enhanced dissociation of the filament (Ellouze et al, ). Of the two possible RecA filament states, only one explains the interaction between LexA and RecA that promotes LexA cleavage (VanLoock et al, ), and the efficient formation of RecA filaments in the active conformation is necessary for SOS induction (Gruenig et al, ).…”
Section: Role Of Dntp Pools In Sos Inductionmentioning
confidence: 99%
“…Little in vivo information is available about the possible role of the cellular dNTPs in RecA activation, although a number of studies have addressed the role of alternative cofactors using in vitro experiments (Phizicky and Roberts, 1981;Weinstock and McEntee, 1981;Menetski et al, 1988;Wang et al, 1988a;Ellouze et al, 1999;Wigle et al, 2006). Various (d)NTP species show different efficiencies in promoting RecA coprotease activity in vitro (Phizicky and Roberts, 1981;Weinstock et al, 1981a).…”
Section: Role Of Dntp Pools In Sos Inductionmentioning
confidence: 99%
“…Other nucleotides are available in vivo , and in vitro experiments show that RecA can bind several of them and retain at least some key functions (McEntee et al ., 1981; Weinstock et al ., 1981a,b,c; Menge and Bryant, 1988; 1992a,b). The nucleotide dATP substitutes best for ATP in vitro , and several RecA functions are enhanced when dATP replaces ATP in reaction mixtures (Menetski and Kowalczykowski, 1989; Shan et al ., 1997; Ellouze et al ., 1999; Robu et al ., 2001).…”
Section: Introductionmentioning
confidence: 99%